(untitled) (Tanzania Medical Journal, 2015)
Background:The prevalence of cardiovascular diseases is increasing in most developing countries, especially in urban settings. Despite this increasing trend, there is limited data on the association between diet and cardiovascular disease risk factors in Tanzania. Objective: To assess the frequency of intake of various foods and explore their relationship with cardiovascular disease risk factors Design: Cross-sectional epidemiological study Study setting: Five randomly selected wards in Temeke district, Dar es Salaam Subjects: Two hundred and nine men and women aged 44-66 years Outcome measures: Blood pressure measured using a standardized digital blood pressure measuring machine, anthropometric measurements, lipid profile and a dietary history which was obtained using a seven-day recall food frequency questionnaire Results: Overall; ugali, tea, green vegetables, white rice, fish and fruits were the most frequently consumed foods in this population. No gender differences were noted in the consumption of the various foods. Overweight and obese participants had significantly higher intakes of beverages, white rice and fruits compared to normal subjects (all p <0.05). Higher monthly income was significantly associated with higher consumption of white rice, meat and fruits (all p<0.05). Frequency of intake of beverages correlated positively and significantly with BMI, total cholesterol and LDL-cholesterol (all p<0.05). Consumption of rice correlated positively with BMI and HDL-cholesterol (all p<0.05) while meat correlated with only BMI (p=0.006). Logistic regression analysis revealed that white rice was the most important dietary determinant of BMI (?=1.91, p=0.038, 95% CI=0.1-3.7) in this population.Conclusion: Consumption of beverages, white rice and meat is associated with obesity in this population. Advocacy on the importance of healthy dietary habits and obesity control as primary and cost-effective intervention is of utmost importance in Tanzania.